Anode foil, preparation method thereof and aluminum electrolytic capacitor

Through microarc oxidation technology and subsequent treatment, a porous alumina film rich in zinc elements is formed, which solves the problems of uneven pore size and poor bending performance on the surface of the anode foil, and improves the specific capacity and bending performance.

CN119296974APending Publication Date: 2025-01-10DONGGUAN DONGYANG SOLAR SCI RES & DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411250295.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The surface pore size distribution and pore length of the anode foil in existing aluminum electrolytic capacitors lead to weakening of specific capacitance and decreasing bending performance, and the corrosion process is complex and uncontrollable.

Method used

Microarc oxidation technology is used to form a porous and orderly aluminum oxide film rich in zinc on the surface of the aluminum foil, and through soaking, electrolytic polishing and hydration treatment, an ultra-thin dense aluminum oxide film rich in fine micropores and orderly distributed is formed. Improve specific capacity and bending performance.

Benefits of technology

The uniformity of the surface pore size distribution and the improvement of zinc element content of the anode foil are achieved, the specific capacity is increased and the bending performance is improved, and the risk of thinning of aluminum foil thickness is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296974A_ABST
    Figure CN119296974A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and particularly relates to an anode foil, a preparation method thereof and an aluminum electrolytic capacitor. The preparation method comprises the following steps: placing an aluminum foil in an electrolytic bath solution containing zinc ions to carry out micro-arc oxidation treatment so as to form a porous aluminum oxide film containing a zinc element on the surface of the aluminum foil; and before hole forming treatment, the aluminum foil subjected to micro-arc oxidation treatment is sequentially subjected to soaking treatment, electrolytic polishing treatment and hydration treatment. According to the preparation method provided by the invention, the anode foil with relatively good specific volume and bending performance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to an anode foil and a preparation method thereof, and an aluminum electrolytic capacitor. Background Art

[0002] Aluminum electrolytic capacitors are widely used in electronic products due to their simple production and stable performance. However, with the continuous evolution of the miniaturization and high-performance requirements of electronic products, aluminum electrolytic capacitors are gradually moving towards a new trend. Anode foil is the main material of aluminum electrolytic capacitors, and improving the specific capacity is the top priority in meeting the challenge. The main way to increase the specific capacity is to increase the effective surface area of ​​the anode foil through corrosion. The process of foil corrosion mainly includes surface treatment of aluminum foil with high purity to remove oil and dirt, electrochemical corrosion to produce holes, hole expansion corrosion to increase the pore diameter and depth, and post-treatment to remove corrosion ions. Due to the large number of operating steps, in the case of corrosion, the pore size distribution and pore depth and length of the aluminum foil surface are highly random, which leads to uneven pore size, different tunnel lengths, weakened specific capacity of the corrosion foil, weakened bending performance, and excessive weight loss during the preparation process.

[0003] To this end, the present invention is proposed. Summary of the invention

[0004] The main purpose of the present invention is to provide an anode foil and a preparation method thereof and an aluminum electrolytic capacitor. The present invention firstly utilizes micro-arc oxidation technology to obtain an aluminum oxide film with a porous and ordered surface and rich in zinc, and combines immersion treatment, electrolytic polishing treatment and hydration treatment to obtain an anode foil with better specific capacitance and bending performance.

[0005] In order to achieve the above objectives, the present invention provides the following technical solutions.

[0006] In a first aspect of the present invention, a method for preparing an anode foil is provided, the method comprising the following steps:

[0007] Placing the aluminum foil in an electrolytic bath containing zinc ions for micro-arc oxidation treatment to form a porous aluminum oxide film containing zinc elements on the surface of the aluminum foil; and

[0008] The aluminum foil after micro-arc oxidation treatment is sequentially subjected to immersion treatment, electrolytic polishing treatment and hydration treatment.

[0009] In some embodiments of the present invention, the concentration of zinc ions in the electrolytic solution is 0.5 g / L to 15 g / L.

[0010] In some embodiments of the present invention, the concentration of zinc ions in the electrolytic solution is 1 g / L to 9 g / L.

[0011] In some embodiments of the present invention, the electrolytic solution is a solution containing zinc sulfate.

[0012] In some embodiments of the present invention, the electrolytic solution is an acidic solution containing zinc sulfate.

[0013] In some embodiments of the present invention, the electrolytic solution contains sulfuric acid and hydrochloric acid.

[0014] In some embodiments of the present invention, the electrolytic cell solution contains 1% to 10% by mass of sulfuric acid and 5% to 20% by mass of hydrochloric acid.

[0015] In some embodiments of the present invention, the electrolytic cell solution contains 3% to 7% by mass of sulfuric acid and 8% to 16% by mass of hydrochloric acid.

[0016] In some embodiments of the present invention, the micro-arc oxidation treatment uses a pulse power supply with a frequency of 1500 Hz to 2500 Hz, a duty cycle of 25% to 40%, and a current density of 45 mA / cm 2 ~75mA / cm 2 .

[0017] In some embodiments of the present invention, the oxidation time of the micro-arc oxidation treatment is 1 min to 15 min.

[0018] In some embodiments of the present invention, the oxidation time of the micro-arc oxidation treatment is 3 minutes to 7 minutes.

[0019] In some embodiments of the present invention, the oxidation voltage of the micro-arc oxidation treatment is 250V to 350V.

[0020] In some embodiments of the present invention, the oxidation voltage of the micro-arc oxidation treatment is 280V to 350V.

[0021] In some embodiments of the present invention, the soaking treatment uses a soaking tank solution containing sulfuric acid and hydrochloric acid.

[0022] In some embodiments of the present invention, the mass percentage of hydrochloric acid in the soaking tank solution is 0.6% to 4.2%, and the mass percentage of sulfuric acid is 15% to 30%.

[0023] In some embodiments of the present invention, the immersion treatment is carried out at a temperature of 30°C to 90°C.

[0024] In some embodiments of the present invention, the temperature of the immersion treatment is 55°C to 65°C.

[0025] In some embodiments of the present invention, the soaking treatment time is 1 min to 10 min.

[0026] In some embodiments of the present invention, the soaking treatment time is 2 minutes to 5 minutes.

[0027] In some embodiments of the present invention, the electrolytic polishing process adopts a constant pressure method.

[0028] In some embodiments of the present invention, the polishing time of the electrolytic polishing treatment is 0.5 min to 8 min.

[0029] In some embodiments of the present invention, the polishing time of the electrolytic polishing treatment is 1 min to 3 min.

[0030] In some embodiments of the present invention, the polishing liquid used in the electrolytic polishing process is a solution containing perchloric acid.

[0031] In some embodiments of the present invention, the mass percentage of perchloric acid in the polishing liquid is 40% to 50%.

[0032] In some embodiments of the present invention, the hydration tank liquid used in the hydration treatment is an aqueous solution containing polyethylene glycol, or an aqueous solution containing ammonia water, or deionized water.

[0033] In some embodiments of the present invention, the mass percentage of the ammonia water is 0.1% to 0.4%.

[0034] In some embodiments of the present invention, the mass ratio of deionized water to polyethylene glycol in the aqueous solution containing polyethylene glycol is 1 to 5:1.

[0035] In some embodiments of the present invention, the temperature of the hydration treatment is 35°C to 90°C.

[0036] In some embodiments of the present invention, the temperature of the hydration treatment is 65°C to 75°C.

[0037] In some embodiments of the present invention, the hydration treatment time is 1 min to 15 min.

[0038] In some embodiments of the present invention, the hydration treatment time is 3 min to 9 min.

[0039] In some embodiments of the present invention, the preparation method further comprises performing a primary pore forming treatment and a secondary pore expanding treatment after the hydration treatment.

[0040] In some embodiments of the present invention, the electrolyte for the primary pore treatment is Al 3+ of acidic solution.

[0041] In some embodiments of the present invention, the temperature of the electrolyte in the primary pore-forming treatment is 60°C to 88°C.

[0042] In some embodiments of the present invention, the primary pore generation process uses a decaying current.

[0043] In some embodiments of the present invention, the initial current density of the primary pore treatment is 1.2 A / cm 2 ~2A / cm 2 After 7s to 12s, the current density decays to 0.4A / cm 2 ~0.7A / cm 2 After 10s to 22s, the current density decays to 0.1A / cm 2 ~0.2A / cm 2 .

[0044] In some embodiments of the present invention, the effective power-on time of the primary pore-forming treatment is 15s to 37s.

[0045] In some embodiments of the present invention, Al in the electrolyte of the primary pore treatment 3+ The mass percentage is 0.7% to 1.3%.

[0046] In some embodiments of the present invention, the electrolyte in the primary pore-forming treatment comprises hydrochloric acid and sulfuric acid.

[0047] In some embodiments of the present invention, the electrolyte of the primary pore-forming treatment contains 0.8% to 4.5% by mass of hydrochloric acid and 25% to 35% by mass of sulfuric acid.

[0048] In some embodiments of the present invention, the electrolyte for the secondary pore expansion treatment is Al 3+ of acidic solution.

[0049] In some embodiments of the present invention, the temperature of the electrolyte in the secondary pore expansion treatment is 65°C to 90°C.

[0050] In some embodiments of the present invention, the current density used in the secondary pore expansion process is 0.04A / cm 2 ~0.25A / cm 2 .

[0051] In some embodiments of the present invention, the effective power-on time of the secondary hole expansion process is 5 minutes to 12 minutes.

[0052] In some embodiments of the present invention, Al in the electrolyte of the secondary pore expansion treatment 3+ The mass percentage is 0.1% to 0.9%.

[0053] In some embodiments of the present invention, the electrolyte of the secondary pore expansion treatment contains phosphoric acid and nitric acid.

[0054] In some embodiments of the present invention, the electrolyte of the secondary pore expansion treatment contains 0.02% to 0.08% by mass of phosphoric acid and 2% to 6.5% by mass of nitric acid.

[0055] In some embodiments of the present invention, the preparation method further comprises post-processing after the secondary pore expansion treatment.

[0056] In some embodiments of the present invention, the treatment solution used in the post-treatment is an aqueous solution containing nitric acid.

[0057] In some embodiments of the present invention, the post-treatment temperature is 60°C to 90°C.

[0058] In some embodiments of the present invention, the post-treatment time is 1 min to 10 min.

[0059] In some embodiments of the present invention, the post-treatment time is 2 min to 5 min.

[0060] In some embodiments of the present invention, the mass percentage of nitric acid in the post-treatment solution is 2% to 11%.

[0061] According to a second aspect of the present invention, an anode foil is provided. The anode foil is prepared by the preparation method according to the first aspect.

[0062] According to a third aspect of the present invention, an aluminum electrolytic capacitor is provided. The aluminum electrolytic capacitor comprises the anode foil according to the second aspect or the anode foil prepared by the preparation method according to the first aspect.

[0063] Compared with the prior art, the present invention achieves the following technical effects:

[0064] (1) The present invention is the first to use an electrolytic bath solution containing zinc ions to perform micro-arc oxidation on aluminum foil, thereby reducing the surface state difference of the aluminum foil, improving the uniformity of the pore size distribution on the surface of the anode foil, and obtaining an aluminum oxide film with a porous and orderly surface and rich in zinc. At the same time, by introducing a trace amount of zinc into the aluminum oxide film on the surface of the aluminum foil, the content and uniformity of the zinc element in the anode foil are increased, and the specific volume is increased.

[0065] (2) In the present invention, an ultra-thin and dense aluminum oxide film rich in fine micropores and orderly distributed is obtained by performing immersion treatment and electrolytic polishing treatment after micro-arc oxidation treatment, thereby improving the specific capacity and bending performance of the anode foil.

[0066] (3) In the present invention, a porous and zinc-rich micro-arc oxidation pit / hydrated composite aluminum film is obtained through hydration, which guides the uniform fine holes on the surface of the aluminum foil to form orderly distributed nucleation sites, improves the uniformity of the pore tunnels, and effectively avoids the risk of thinning the aluminum foil.

[0067] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings:

[0069] Figure 1 Surface morphology of a micro-arc aluminum oxide film according to some embodiments of the present invention;

[0070] Figure 2 A cross-sectional distribution diagram of Zn elements in a micro-arc aluminum oxide film according to some embodiments of the present invention;

[0071] Figure 3 This is a surface morphology image of the corroded foil obtained in Example 6 of the present invention;

[0072] Figure 4 This is a cross-sectional morphology of the corroded foil obtained in Example 6 of the present invention. DETAILED DESCRIPTION

[0073] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0074] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0075] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0076] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0077] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0078] At present, after the aluminum foil is treated by general electrochemical process, the surface of the aluminum foil is severely thinned, the pore size distribution is uneven, and the pore length is different, which leads to the weakening of the specific volume and bending performance of the corrosion foil, and excessive weight loss. In order to improve the uniformity of the pore size distribution on the surface of the aluminum foil and increase the pore-forming efficiency, one of the commonly used solutions is to adjust the surface state of the aluminum foil. For example, some technologies generate an orderly porous aluminum oxide film on the surface of the high-voltage aluminum foil by anodizing, dissolve the aluminum oxide film and expose the highly ordered nano-pits on the aluminum foil substrate, and use the pits to regulate the nucleation position of the tunnel hole during the aluminum foil corrosion pore formation, so as to improve the distribution uniformity of the tunnel hole and achieve the effect of increasing the specific volume. However, although the pore size distribution uniformity of the porous aluminum film prepared by the anodizing method is improved, the performance of the generated aluminum film is poor, which is greatly affected by temperature, and it is easy to have surface cracks and uneven local pore size, and the morphology performance is poor; and the method of removing the surface aluminum oxide film is also random and uncontrollable, which is easy to leave residual aluminum film, thereby inhibiting the nucleation and growth of the corrosion tunnel hole, which is not conducive to pore formation and has a counter-effect. Therefore, it is crucial to develop a suitable method to obtain medium- and high-voltage anode foils with orderly arrangement, uniform tunnel pore length, consistent pore size, and better specific volume and bending properties.

[0079] Micro-arc oxidation is an effective surface treatment technology. It mainly reacts in situ on the surface of metals and alloys to form a film layer mainly composed of metal oxides. In the process of reaction, it is often accompanied by chemical oxidation, electrochemical oxidation, and plasma oxidation. Under the condition of repeated breakdown discharge, a porous film layer with loose outside and dense inside is continuously formed. Compared with traditional surface treatment technologies such as anodizing and electroplating, micro-arc oxidation can extend the voltage value from the Faraday region to the spark discharge region of the substrate, prompting certain metal ions in the electrolyte to act on the surface of the substrate and participate in the formation of the film layer in the arc discharge, thereby making the film layer more dense and uniform, with better performance and more special; in addition, the micro-arc oxidation process is relatively simple and convenient, and no acid or alkali washing or other treatments are required before the experiment.

[0080] The invention discloses a method for preparing an anode foil, which comprises placing an aluminum foil in an electrolytic bath solution containing zinc ions for micro-arc oxidation treatment to form a porous aluminum oxide film containing zinc elements on the surface of the aluminum foil; and before performing a pore forming treatment, sequentially performing an immersion treatment, an electrolytic polishing treatment and a hydration treatment on the aluminum foil after the micro-arc oxidation treatment.

[0081] Micro-arc oxidation treatment

[0082] The present invention is the first to use micro-arc oxidation technology to oxidize aluminum foil using an electrolytic bath solution containing zinc ions, thereby reducing the surface state difference of the aluminum foil, improving the uniformity of the pore size distribution on the surface of the aluminum foil, and obtaining an anode aluminum film with a porous and orderly surface and rich in zinc. At the same time, by introducing trace zinc into the aluminum oxide film on the surface of the aluminum foil, the content and uniformity of zinc in the electrode foil are increased, and the specific volume is increased.

[0083] In some embodiments of the present invention, micro-arc oxidation equipment is used, and zinc ions are added to the electrolytic bath to obtain an aluminum oxide film containing zinc elements. In some embodiments, the concentration of zinc ions in the electrolytic bath containing zinc ions is 0.5 g / L to 15 g / L, thereby forming an aluminum oxide film rich in zinc elements. The zinc ion concentration provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 0.5 g / L to 1 g / L, 1 g / L to 5 g / L, 1 g / L to 9 g / L, 5 g / L to 9 g / L, 9 g / L to 15 g / L, and so on. The zinc ion concentration provided by the present invention can also be one of 0.5g / L, 1g / L, 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, 11g / L, 12g / L, 13g / L, 14g / L, 15g / L or any value that meets the above range.

[0084] In some embodiments of the present invention, the electrolytic bath liquid of micro-arc oxidation is a solution containing zinc sulfate.

[0085] In some embodiments of the present invention, the electrolytic bath liquid of micro-arc oxidation is an acidic solution containing zinc sulfate.

[0086] In some embodiments of the present invention, the electrolytic cell liquid of micro-arc oxidation contains sulfuric acid and hydrochloric acid, for example, the electrolytic cell liquid contains 1% to 10% sulfuric acid and 5% to 20% hydrochloric acid by mass. The mass percentage of sulfuric acid provided by the present invention can be the value of the interval composed of any two values ​​in the above interval, such as 1% to 3%, 3% to 7%, 7% to 10%, and so on. Exemplarily, the mass percentage of sulfuric acid in the electrolytic cell liquid can be one of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value that satisfies the above range value. The mass percentage of hydrochloric acid provided by the present invention can be the value of the interval composed of any two values ​​in the above interval, such as 5% to 8%, 8% to 16%, 16% to 20%, and so on. Exemplarily, the mass percentage of hydrochloric acid in the electrolytic cell liquid can be one of 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any value that meets the above range.

[0087] It is worth mentioning that the electrolytic bath liquid of the micro-arc oxidation in the present invention is a solution containing sulfuric acid, hydrochloric acid and zinc sulfate. On the basis that the acidic solution is sulfuric acid and hydrochloric acid, the use of zinc sulfate can avoid the introduction of other impurity ions. However, the electrolytic bath liquid in the present invention is not limited to the acidic solution and zinc salt described above. In practical applications, suitable zinc salts and acidic solutions can be adjusted as needed.

[0088] In some embodiments of the present invention, micro-arc oxidation uses an electrolytic bath solution composed of sulfuric acid, hydrochloric acid and zinc sulfate, wherein the concentration of zinc sulfate is 0.5 g / L to 15 g / L, the mass percentage of sulfuric acid is 1% to 10%, and the mass percentage of hydrochloric acid is 5% to 20%.

[0089] In some embodiments of the present invention, micro-arc oxidation uses an electrolytic bath solution composed of sulfuric acid, hydrochloric acid and zinc sulfate, wherein the concentration of zinc sulfate is 1 g / L to 9 g / L, the mass percentage of sulfuric acid is 3% to 7% and the mass percentage of hydrochloric acid is 8% to 16%.

[0090] In some embodiments of the present invention, the micro-arc oxidation treatment uses a pulse power supply with a frequency of 1500 Hz to 2500 Hz, a duty cycle of 25% to 40%, and a current density of 45 mA / cm 2 ~75mA / cm 2. The frequency of the pulse power supply provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 1500Hz~2000Hz, or it can be 2000Hz~2500Hz, and so on. The frequency of the pulse power supply provided by the present invention can also be one of 1500Hz, 1600Hz, 1700Hz, 1800Hz, 1900Hz, 2000Hz, 2100Hz, 2200Hz, 2300Hz, 2400Hz, 2500Hz or any value that satisfies the above range value. The duty cycle of the pulse power supply provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 25%~30%, or it can be 30%~40%, and so on. The duty cycle of the pulse power supply provided by the present invention can also be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40% or any value that meets the above range. The current density of the pulse power supply provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 45mA / cm 2 ~60mA / cm 2 , or 60mA / cm 2 ~75mA / cm 2 , and so on. The current density of the pulse power supply provided by the present invention can also be 45mA / cm 2 , 50mA / cm 2 , 55mA / cm 2 、60mA / cm 2 、65mA / cm 2 , 70mA / cm 2 , 75mA / cm 2 or any value that satisfies the above range.

[0091] For example, the micro-arc oxidation treatment uses a pulse power supply with a frequency of 2000 Hz, a duty cycle of 35%, and a current density of 60 mA / cm 2 .

[0092] In some embodiments of the present invention, the oxidation time of the micro-arc oxidation treatment is 1 min to 15 min. The oxidation time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 1 min to 3 min, it can be 3 min to 7 min, it can also be 7 min to 15 min, and so on. The oxidation time provided by the present invention can also be one of 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min or any value that meets the above range value.

[0093] In some embodiments of the present invention, the oxidation voltage of the micro-arc oxidation treatment is 250V to 350V. The oxidation voltage provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 250V to 280V, it can be 280V to 350V, it can be 250V to 300V, it can be 300V to 350V, and so on. The oxidation voltage provided by the present invention can also be one of 250V, 260V, 270V, 280V, 290V, 300V, 310V, 320V, 330V, 340V, 350V or any value that meets the above range value.

[0094] Therefore, by adjusting the oxidation parameters and the electrolytic bath solution as above, the aluminum foil is subjected to micro-arc oxidation treatment to form a porous, ordered, Zn-rich aluminum oxide film.

[0095] Soaking treatment

[0096] In the present invention, the loose layer with slightly poor surface morphology and part of the corrosion products of the aluminum oxide film are removed by immersion treatment, leaving a dense layer of the aluminum oxide film with uniform fine micropores and rich in zinc, thereby improving the specific volume and bending performance of the anode foil.

[0097] In some embodiments of the present invention, the immersion treatment uses an immersion bath containing sulfuric acid and hydrochloric acid, thereby obtaining an ultra-thin and dense aluminum oxide film rich in fine micropores and orderly distributed.

[0098] In some embodiments of the present invention, the mass percentage of hydrochloric acid in the soaking tank solution is 0.6% to 4.2%, and the mass percentage of sulfuric acid is 15% to 30%. The mass percentage of hydrochloric acid in the soaking tank solution provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 0.6% to 2.0%, or 2.0% to 4.2%, and so on. The mass percentage of hydrochloric acid in the soaking tank solution provided by the present invention can also be 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2% or any value that meets the above range value. The mass percentage of sulfuric acid in the soaking tank provided by the present invention can be a value in the interval composed of any two values ​​in the above range, for example, it can be 15% to 25%, or it can be 25% to 30%, and so on. The mass percentage of sulfuric acid in the soaking tank provided by the present invention can also be one of 15%, 18%, 20%, 22%, 24%, 26%, 28%, 30% or any value that meets the above range.

[0099] In some embodiments of the present invention, the temperature of the immersion treatment is 30°C to 90°C. The temperature of the immersion treatment provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 30°C to 55°C, 55°C to 65°C, or 65°C to 90°C, and so on. The temperature of the immersion treatment provided by the present invention can be one of 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value that satisfies the above range value. In some embodiments of the present invention, the time of the immersion treatment is 1min to 10min. The time of the immersion treatment provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 2min to 5min, or 5min to 10min, and so on. The soaking treatment time provided by the present invention can be one of 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min or any value that meets the above range.

[0100] In the present invention, by adjusting the above-mentioned parameters such as the immersion tank liquid, a suitable surface state of the aluminum foil is provided to form an ultra-thin dense layer aluminum film that is porous, orderly and rich in zinc.

[0101] Electrolytic polishing

[0102] In the present invention, the loose layer with slightly poor surface morphology and part of the corrosion products of the aluminum oxide film are removed by immersion treatment and electrolytic polishing treatment, leaving a dense layer of aluminum oxide film with uniform fine micropores and rich in zinc, thereby improving the specific volume and bending performance of the anode foil.

[0103] In some embodiments of the present invention, the electrolytic polishing process uses a constant pressure method.

[0104] In some embodiments of the present invention, the voltage of the constant voltage method is 3 V to 7 V. Exemplarily, the voltage used in the electrolytic polishing process can be one of 3 V, 4 V, 5 V, 6 V, 7 V or any value that satisfies the above range.

[0105] In some embodiments of the present invention, the polishing time of the electrolytic polishing treatment is 0.5 min to 8 min, and the polishing time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 1 min to 3 min, or 3 min to 8 min, and so on. Exemplarily, the polishing time provided by the present invention can be one of 0.5 min, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, or any value that satisfies the above range.

[0106] In some embodiments of the present invention, the polishing liquid used in the electrolytic polishing process is a solution containing perchloric acid.

[0107] In some embodiments of the present invention, the mass percentage of perchloric acid in the polishing liquid is 40% to 50%. Exemplarily, the mass percentage of perchloric acid in the polishing liquid provided by the present invention can be one of 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or any value that meets the above range.

[0108] In the present invention, by adjusting the above-mentioned relevant parameters such as immersion and electrolytic polishing treatment, a suitable surface state of the aluminum foil is provided to form an ultra-thin dense layer aluminum oxide film that is porous, orderly and rich in zinc.

[0109] Hydration treatment

[0110] In the present invention, the dense layer aluminum oxide film obtained after electrolytic polishing is hydrated to form a porous and zinc-rich micro-arc oxidation pit / hydrated composite aluminum film, which guides the uniform fine holes on the surface of the aluminum foil to form orderly nucleation sites, constructs the corresponding aluminum film pit template, and improves corrosion pore formation with the assistance of zinc.

[0111] In some embodiments of the present invention, the hydration bath solution used in the hydration treatment is an aqueous solution containing polyethylene glycol.

[0112] In some embodiments of the present invention, the mass ratio of deionized water to polyethylene glycol in the aqueous solution containing polyethylene glycol is 1 to 5: 1. Exemplarily, the mass ratio of deionized water to polyethylene glycol in the aqueous solution containing polyethylene glycol can be one of 1: 1, 2: 1, 3: 1, 4: 1, 5: 1 or any value satisfying the above range.

[0113] In some embodiments of the present invention, the hydration bath solution used in the hydration treatment is an aqueous solution containing ammonia water.

[0114] In some embodiments of the present invention, the mass percentage of ammonia in the aqueous solution containing ammonia is 0.1% to 0.4%. For example, the mass percentage of ammonia can be one of 0.1%, 0.2%, 0.3%, 0.4% or any value satisfying the above range.

[0115] In some embodiments of the present invention, the hydration bath solution used in the hydration treatment is deionized water.

[0116] In some embodiments of the present invention, the temperature of the hydration treatment is 35°C to 90°C, and the temperature of the hydration treatment provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 35°C to 65°C, 65°C to 75°C, or 75°C to 90°C, and so on. Exemplarily, the temperature of the hydration treatment can be 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 80°C, 85°C, 90°C or any value that satisfies the above range. In some embodiments of the present invention, the time of the hydration treatment is 1min to 15min, and the time of the hydration treatment provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 3min to 9min, or 9min to 15min, and so on. Exemplarily, the hydration treatment time can be one of 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, or any value that meets the above range.

[0117] In the present invention, by adjusting the relevant parameters of hydration as mentioned above, a Zn-rich micro-arc oxidation pit / hydrated composite aluminum film is obtained, a template is constructed, and nucleation sites are guided to form on the surface of the aluminum foil, thereby assisting the aluminum foil in corrosion and pore formation under double protection.

[0118] First-level pore treatment

[0119] In the present invention, the aluminum foil after hydration treatment is subjected to primary pore forming treatment and secondary pore expanding treatment.

[0120] In some embodiments of the present invention, the electrolyte for the primary pore treatment is Al 3+ of acidic solution.

[0121] In some embodiments of the present invention, Al in the electrolyte of the primary pore treatment 3+ The mass percentage of Al in the electrolyte of the primary pore treatment provided by the present invention is 0.1% to 2.5%. 3+ The mass percentage of can be a value in the interval formed by any two values ​​in the above range, for example, it can be 0.7% to 1.3%, or 1.3% to 2.5%, and so on. 3+ The mass percentage can be one of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5% or any value that meets the above range.

[0122] In some embodiments of the present invention, the electrolyte in the primary pore-forming treatment comprises hydrochloric acid and sulfuric acid.

[0123] In some embodiments of the present invention, the electrolyte of the primary pore treatment contains 0.8% to 4.5% by mass of hydrochloric acid and 25% to 35% by mass of sulfuric acid. Exemplarily, the mass percentage of hydrochloric acid in the electrolyte of the primary pore treatment can be 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.5% or any value that meets the above range. The mass percentage of sulfuric acid in the electrolyte of the primary pore treatment can be one of 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or any value that meets the above range.

[0124] In some embodiments of the present invention, the electrolyte for the primary pore treatment is composed of hydrochloric acid (HCl), sulfuric acid (H2SO4) and Al 3+ The composition is as follows: the mass percentage of HCl is 0.8% to 4.5%, the mass percentage of H2SO4 is 25% to 35%, and the mass percentage of Al 3+The mass percentage is 0.1% to 2.5%.

[0125] In some embodiments of the present invention, the electrolyte for the primary pore treatment is composed of hydrochloric acid (HCl), sulfuric acid (H2SO4) and Al 3+ The composition is as follows: the mass percentage of HCl is 0.8% to 4.5%, the mass percentage of H2SO4 is 25% to 35%, and the mass percentage of Al 3+ The mass percentage is 0.7% to 1.3%.

[0126] In some embodiments of the present invention, the temperature of the electrolyte of the primary pore treatment is 60°C to 88°C. Exemplarily, the temperature of the electrolyte of the primary pore treatment can be a value of an interval composed of any two values ​​in the above interval, such as 60°C to 70°C, or 70°C to 88°C, and so on. The temperature of the electrolyte of the primary pore treatment can also be one of 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or any value that satisfies the above range.

[0127] In some embodiments of the present invention, the primary pore generation process uses a decaying current.

[0128] In some embodiments of the present invention, the initial current density of the primary pore treatment is 1.2 A / cm 2 ~2A / cm 2 After 7s to 12s, the current density decays to 0.4A / cm 2 ~0.7A / cm 2 After 10s to 22s, the current density decays to 0.1A / cm 2 ~0.2A / cm 2 .

[0129] For example, the initial current density in the primary pore treatment provided by the present invention may be 1.2 A / cm 2 , 1.3A / cm 2 , 1.4A / cm 2 , 1.5A / cm 2 , 1.6A / cm 2 , 1.7A / cm 2 , 1.8A / cm 2 , 1.9A / cm 2 , 2A / cm 2 One of the above or any value that meets the above range. After 7s to 12s, the current density decays to 0.4A / cm 2 , 0.5A / cm 2 , 0.6A / cm 2 , 0.7A / cm2 One of the above or any value that meets the above range. After 10s to 22s, the current density decays to 0.1A / cm 2 or 0.2A / cm 2 .

[0130] In some embodiments of the present invention, the effective power-on time of the primary pore treatment is 15s to 37s. Exemplarily, the effective power-on time of the primary pore treatment can be a value of an interval consisting of any two values ​​in the above interval, such as 15s to 25s, or 25s to 37s, and so on. The effective power-on time of the primary pore treatment can also be one of 15s, 18s, 20s, 22s, 25s, 28s, 30s, 32s, 35s, 37s, or any value that satisfies the above range.

[0131] Secondary hole expansion

[0132] In the present invention, the aluminum foil after the primary pore forming treatment is subjected to a secondary pore expanding treatment. In some embodiments of the present invention, the electrolyte for the secondary pore expanding treatment is Al 3+ of acidic solution.

[0133] In some embodiments of the present invention, Al in the electrolyte of the secondary pore expansion process 3+ The mass percentage of Al in the electrolyte of the secondary pore expansion treatment is 0.1% to 0.9%. 3+ The mass percentage can be one of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or any value satisfying the above range.

[0134] In some embodiments of the present invention, the electrolyte for the secondary pore expansion treatment contains nitric acid and phosphoric acid.

[0135] In some embodiments of the present invention, the electrolyte of the secondary pore expansion treatment contains 0.02% to 0.08% by mass of phosphoric acid and 2% to 6.5% by mass of nitric acid (HNO3). Exemplarily, the mass percentage of phosphoric acid in the electrolyte of the secondary pore expansion treatment can be one of 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08% or any value that satisfies the above range value. The mass percentage of nitric acid in the electrolyte of the secondary pore expansion treatment can be a value of an interval composed of any two values ​​in the above interval, such as 2% to 3.5%, or 3.5% to 6.5%, and so on. The mass percentage of nitric acid in the electrolyte of the secondary pore expansion treatment can also be one of 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, 5.2%, 5.4%, 5.6%, 5.8%, 6%, 6.2%, 6.5% or any value that meets the above range.

[0136] In some embodiments of the present invention, the electrolyte for the secondary pore expansion treatment is composed of nitric acid, phosphoric acid and Al 3+ The mass percentage of phosphoric acid is 0.02% to 0.08%, the mass percentage of nitric acid is 2% to 6.5%, and the mass percentage of Al 3+ The mass percentage is 0.1% to 0.9%.

[0137] In some embodiments of the present invention, the temperature of the electrolyte in the secondary pore expansion treatment is 65° C. to 90° C. For example, the temperature of the electrolyte in the secondary pore expansion treatment may be one of 65° C., 66° C., 67° C., 68° C., 69° C., 70° C., 71° C., 72° C., 73° C., 74° C., 75° C., 80° C., 85° C., 90° C., or any value satisfying the above range.

[0138] In some embodiments of the present invention, the current density used in the secondary pore expansion process may be 0.04 A / cm 2 ~0.25A / cm 2 For example, the current density used in the secondary hole expansion process may be 0.04A / cm 2 , 0.05A / cm 2 , 0.06A / cm 2 , 0.07A / cm 2 , 0.08A / cm 2 , 0.09A / cm 2 , 0.1A / cm 2 , 0.12A / cm 2 , 0.14A / cm 2 , 0.16A / cm2 , 0.18A / cm 2 , 0.2A / cm 2 , 0.22A / cm 2 , 0.25A / cm 2 or any value that satisfies the above range.

[0139] In some embodiments of the present invention, the effective power-on time of the secondary hole expansion process is 5 minutes to 12 minutes. Exemplarily, the effective power-on time of the secondary hole expansion process can be one of 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, or any value satisfying the above range.

[0140] Post-processing

[0141] In the present invention, considering the corrosiveness of chloride ions, in order to avoid residual chloride ions, the anode foil that has completed the secondary hole expansion treatment is post-treated according to actual conditions.

[0142] In some embodiments of the present invention, the treatment solution used in the post-treatment is an aqueous solution containing nitric acid.

[0143] In some embodiments of the present invention, the mass percentage of nitric acid in the post-treatment solution is 2% to 11%. For example, the mass percentage of nitric acid in the post-treatment solution can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11% or any value satisfying the above range.

[0144] In some embodiments of the present invention, the temperature of the post-treatment is 60°C to 90°C. Exemplarily, the temperature of the post-treatment can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 85°C, 90°C or any numerical value that satisfies the above range value. In some embodiments of the present invention, the time of post-treatment is 1min to 10min, and the time of post-treatment provided by the present invention can be the value of the interval composed of any two values ​​in the above interval, such as 2min to 5min, or 5min to 10min, and so on. Exemplarily, the time of post-treatment can be 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min or any numerical value that satisfies the above range value.

[0145] In some embodiments of the present invention, the post-treatment is performed in an aqueous solution of nitric acid containing 2% to 11% by mass at a temperature of 60° C. to 90° C. for 1 min to 10 min.

[0146] In some embodiments of the present invention, the post-treatment is carried out in an aqueous solution of nitric acid containing 2% to 11% by mass at a temperature of 60° C. to 90° C. for 2 min to 5 min.

[0147] In some embodiments of the present invention, a method for preparing an anode foil is provided, the method comprising the following steps:

[0148] S1. Micro-arc oxidation treatment: placing the aluminum foil in an electrolytic bath containing zinc ions for micro-arc oxidation treatment to form a porous aluminum oxide film containing zinc elements on the surface of the aluminum foil;

[0149] S2, soaking treatment: placing the aluminum foil after micro-arc oxidation treatment in a soaking tank liquid; and

[0150] S3, electrolytic polishing treatment: placing the aluminum foil after immersion treatment in a polishing solution for electrolytic polishing treatment to obtain an ultra-thin and dense aluminum oxide film rich in fine micropores and orderly distributed;

[0151] S4, hydration treatment: hydrating the aluminum foil after electrolytic polishing to form a porous and zinc-rich micro-arc oxidation pit / hydrated composite aluminum film;

[0152] S5, primary pore forming treatment: subjecting the hydrated aluminum foil to a primary pore forming treatment; and

[0153] S6, secondary hole expansion treatment: the aluminum foil after the primary hole expansion treatment is subjected to secondary hole expansion treatment;

[0154] S7, post-processing: post-process the aluminum foil after the secondary hole expansion treatment to avoid residual chloride ions.

[0155] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0156] Example 1

[0157] Disclosed is a method for preparing an anode aluminum foil, the method comprising the following steps:

[0158] S1. Micro-arc oxidation treatment: After 10 minutes of ultrasound treatment, the aluminum foil with a purity of 99.99% was placed in an electrolytic bath solution (5% sulfuric acid and 10% hydrochloric acid + zinc sulfate with a concentration of 1g / L) for micro-arc oxidation for 3.5 minutes at a working voltage of 280V to generate a porous aluminum oxide film containing zinc on the surface of the aluminum foil (the micro-arc oxidation equipment uses a pulse power supply with a frequency of 2000Hz, a duty cycle of 35%, and a current density of 60mA / cm 2 ).

[0159] S2. Soaking treatment: Soak the aluminum foil having a porous aluminum oxide film containing zinc element in a mixed acid bath (2% by mass hydrochloric acid + 20% by mass sulfuric acid) at 60° C. for 3 minutes.

[0160] S3. Electrolytic polishing: The aluminum foil after immersion treatment is electrolytically polished for 2 minutes using a constant voltage method with a voltage of 5V and a polishing liquid of 45% by mass of a perchloric acid aqueous solution to remove the loose layer with poor pore size distribution on the surface of the aluminum oxide film to obtain an ultra-thin and dense aluminum oxide film rich in zinc and orderly porous.

[0161] S4. Hydration treatment: The aluminum foil that has been electropolished is placed in deionized water at 65° C. for hydration treatment for 5 minutes to obtain a uniformly distributed micro-arc oxidation pit / hydrated composite aluminum film.

[0162] S5, primary pore treatment: place the hydrated aluminum foil in a pore-forming electrolyte (HCl+H2SO4+Al 3 + The first-level pore formation treatment was carried out in an aqueous solution (the initial current density was 1.5 A / cm 2 After 10s, the current density decayed to 0.5A / cm 2 After 20s, the current density decayed to 0.2A / cm 2 ), the effective power-on time is 30s, where the mass percentage of HCl is 3%, the mass percentage of H2SO4 is 30%, and the mass percentage of Al 3+ The mass percentage is 1.0%.

[0163] S6, secondary pore expansion treatment: The aluminum foil that has completed the primary pore expansion treatment is placed in a pore expansion electrolyte (nitric acid + phosphoric acid + Al 3+ ) for secondary pore expansion, with a current density of 0.2 mA / cm 2 , the effective power-on time is 7 minutes, among which the mass percentage of HNO3 is 4%, the mass percentage of phosphoric acid is 0.06%, and the mass percentage of Al 3+ The mass percentage is 0.5%.

[0164] S7, post-treatment: at a temperature of 65°C, the aluminum foil that has completed the secondary hole expansion treatment is placed in an aqueous solution containing 8% by mass of nitric acid for post-treatment for 4 minutes, rinsed and dried, and then subjected to 520V chemical formation to obtain an anode aluminum foil.

[0165] Example 2

[0166] The remaining operations are the same as those in Example 1, and the only difference from Example 1 is that:

[0167] S1. Micro-arc oxidation treatment: the concentration of zinc sulfate is 3 g / L.

[0168] Example 3

[0169] The remaining operations are the same as those in Example 1, and the only difference from Example 1 is that:

[0170] S1. Micro-arc oxidation treatment: the concentration of zinc sulfate is 5 g / L.

[0171] Example 4

[0172] The remaining operations are the same as those in Example 1, and the only difference from Example 1 is that:

[0173] S1, micro-arc oxidation treatment: the concentration of zinc sulfate is 3g / L;

[0174] S4. Hydration treatment: The hydration treatment lasts for 7 minutes.

[0175] Example 5

[0176] The remaining operations are the same as those in Example 1, and the only difference from Example 1 is that;

[0177] S1, micro-arc oxidation treatment: the concentration of zinc sulfate is 3g / L;

[0178] S4. Hydration treatment: The hydration treatment lasts for 9 minutes.

[0179] Example 6

[0180] The remaining operations are the same as those in Example 1, and the only difference from Example 1 is that;

[0181] S1, micro-arc oxidation treatment: the concentration of zinc sulfate is 3g / L;

[0182] S5, primary pore treatment: the electrolyte temperature is 65°C.

[0183] Example 7

[0184] The remaining operations are the same as those in Example 1, and the only difference from Example 1 is that:

[0185] S1, micro-arc oxidation treatment: the concentration of zinc sulfate is 3g / L;

[0186] S5, primary pore treatment: the electrolyte temperature is 68°C.

[0187] Example 8

[0188] The remaining operations are the same as those in Example 1, and the only difference from Example 1 is that:

[0189] S1, micro-arc oxidation treatment: the concentration of zinc sulfate is 9g / L;

[0190] S4, hydration treatment: the hydration treatment duration is 7 minutes;

[0191] S5, primary pore treatment: the electrolyte temperature is 80°C.

[0192] Comparative Example 1

[0193] The remaining operations are the same as those in Example 1, except that:

[0194] Replace S1, micro-arc oxidation treatment with the following steps:

[0195] S1. Soak in a solution of 5% sulfuric acid + 10% hydrochloric acid + 1g / L zinc sulfate for 3.5 minutes.

[0196] Comparative Example 2

[0197] The remaining operations are the same as those in Example 1, except that:

[0198] S1. Micro-arc oxidation treatment: an aluminum foil with a purity of 99.99% after ultrasonic treatment for 10 minutes is placed in an electrolytic bath solution (5% by mass sulfuric acid and 10% by mass hydrochloric acid, without adding zinc sulfate to the electrolytic bath solution) for micro-arc oxidation for 3.5 minutes at a working voltage of 280 V to generate a porous aluminum oxide film containing zinc on the surface of the aluminum foil.

[0199] Comparative Example 3

[0200] The remaining operations are the same as those in Example 1, except that S1 and micro-arc oxidation treatment are not performed.

[0201] Performance Testing

[0202] The specific volume of the formed aluminum foil was measured by a multi-frequency LCR digital bridge meter (ZB23080523, Changzhou Zhixin Precision Electronics Co., Ltd.) at 30°C with an 80 g / L ammonium pentaborate solution at a setting frequency of 120 Hz. The bending performance was tested by a strength tester (Japan, specification model MIT-D) at an angle of 90 degrees, a speed of 360 times, and a curvature radius of 1.0.

[0203] Table 1 Summary of specific volume and bending properties of anode foils obtained in the embodiments of the present invention and comparative examples

[0204]

[0205]

[0206] Figure 1 and Figure 2 The surface morphology of the aluminum oxide film obtained after the aluminum foil is subjected to micro-arc oxidation treatment in the embodiment of the present invention and the distribution diagram of the Zn element in the aluminum oxide film. Figure 1 and Figure 2 It can be seen that the pore size distribution on the surface of the aluminum oxide film is uniform and the Zn element is evenly distributed.

[0207] Figure 3 is a surface morphology of the anode foil obtained in Example 6 of the present invention, Figure 4 This is a cross-sectional morphology of the surface of the anode foil prepared in Example 6 of the present invention.

[0208] Combining Table 1 and Figure 3 to Figure 4 It can be seen that the tunnel holes of the anode foil prepared in the present invention are uniform in length, and the thickness of the middle sandwich layer of the anode foil is consistent, that is, the anode foil has a higher specific volume and better bending performance; with the formation of the micro-arc oxidation pit / hydrated composite aluminum film template, the uniformity of the distribution of etching holes on the surface of the aluminum foil is further improved, and with the assistance of trace Zn elements, the specific volume and bending performance of the anode foil are higher.

[0209] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope required by the specification of the rights.

Claims

1. A method for preparing an anode foil, characterized in that: The preparation method comprises the following steps: Placing the aluminum foil in an electrolytic bath containing zinc ions for micro-arc oxidation treatment to form a porous aluminum oxide film containing zinc elements on the surface of the aluminum foil; and The aluminum foil after micro-arc oxidation treatment is sequentially subjected to immersion treatment, electrolytic polishing treatment and hydration treatment.

2. The method for preparing an anode foil according to claim 1, characterized in that: The concentration of zinc ions in the electrolytic bath solution is 0.5 g / L to 15 g / L, preferably 1 g / L to 9 g / L; Preferably, the electrolytic bath solution is a solution containing zinc sulfate; Preferably, the electrolytic bath solution is an acidic solution containing zinc sulfate; More preferably, the electrolytic cell solution contains sulfuric acid and hydrochloric acid; More preferably, the electrolytic bath solution contains 1% to 10% by mass of sulfuric acid and 5% to 20% by mass of hydrochloric acid; More preferably, the electrolytic cell solution contains 3% to 7% by mass of sulfuric acid and 8% to 16% by mass of hydrochloric acid.

3. The method for preparing an anode foil according to claim 1, characterized in that: The micro-arc oxidation treatment uses a pulse power supply with a frequency of 1500 Hz to 2500 Hz, a duty cycle of 25% to 40%, and a current density of 45 mA / cm 2 ~75mA / cm 2 ; Preferably, the oxidation time of the micro-arc oxidation treatment is 1 min to 15 min; preferably 3 min to 7 min; Preferably, the oxidation voltage of the micro-arc oxidation treatment is 250V to 350V; preferably 280V to 350V.

4. The method for preparing an anode foil according to claim 1, characterized in that: The soaking treatment uses a soaking tank solution containing sulfuric acid and hydrochloric acid; Preferably, the mass percentage of hydrochloric acid in the soaking tank solution is 0.6% to 4.2%, and the mass percentage of sulfuric acid is 15% to 30%; Preferably, the soaking temperature is 30°C to 90°C; preferably 55°C to 65°C; Preferably, the soaking treatment time is 1 min to 10 min; preferably 2 min to 5 min.

5. The method for preparing an anode foil according to claim 1, characterized in that: The electrolytic polishing treatment adopts a constant voltage method; the voltage of the constant voltage method is preferably 3v to 7v; Preferably, the polishing time of the electrolytic polishing treatment is 0.5 min to 8 min; preferably 1 min to 3 min; Preferably, the polishing liquid used in the electrolytic polishing treatment is a solution containing perchloric acid; Preferably, the mass percentage of perchloric acid in the polishing liquid is 40% to 50%.

6. The method for preparing an anode foil according to claim 1, characterized in that: The hydration tank liquid used in the hydration treatment is an aqueous solution containing polyethylene glycol, or an aqueous solution containing ammonia water, or deionized water; Preferably, the mass percentage of the ammonia water is 0.1% to 0.4%; Preferably, the mass ratio of deionized water to polyethylene glycol in the aqueous solution containing polyethylene glycol is 1 to 5:1; Preferably, the temperature of the hydration treatment is 35°C to 90°C; preferably 65°C to 75°C; Preferably, the hydration treatment time is 1 min to 15 min; preferably 3 min to 9 min.

7. The method for preparing an anode foil according to claim 1, characterized in that: The preparation method further comprises performing a primary pore forming treatment and a secondary pore expanding treatment after the hydration treatment; Preferably, the electrolyte for the primary pore treatment contains Al 3+ Acidic solution; Preferably, the temperature of the electrolyte in the primary pore treatment is 60°C to 88°C; Preferably, the primary pore treatment uses a decaying current; Preferably, the initial current density of the primary pore treatment is 1.2 A / cm 2 ~2A / cm 2 After 7s to 12s, the current density decays to 0.4A / cm 2 ~0.7A / cm 2 After 10s to 22s, the current density decays to 0.1A / cm 2 ~0.2A / cm 2 ; Preferably, the effective power-on time of the first-level pore treatment is 15s to 37s; Preferably, the electrolyte of the first-stage pore treatment contains Al 3+ The mass percentage is 0.1% to 2.5%, preferably 0.7% to 1.3%; Preferably, the electrolyte in the primary pore-forming treatment comprises hydrochloric acid and sulfuric acid; Preferably, the electrolyte of the primary pore treatment contains 0.8% to 4.5% by mass of hydrochloric acid and 25% to 35% by mass of sulfuric acid; Preferably, the electrolyte for the secondary pore expansion treatment contains Al 3+ Acidic solution; Preferably, the temperature of the electrolyte in the secondary pore expansion treatment is 65°C to 90°C; Preferably, the current density used in the secondary hole expansion process is 0.04A / cm 2 ~0.25A / cm 2 ; Preferably, the effective power-on time of the secondary hole expansion treatment is 5 minutes to 12 minutes; Preferably, the electrolyte of the secondary pore expansion treatment contains Al 3+ The mass percentage is 0.1% to 0.9%; Preferably, the electrolyte in the secondary pore expansion treatment contains phosphoric acid and nitric acid; Preferably, the electrolyte of the secondary pore expansion treatment contains 0.02% to 0.08% by mass of phosphoric acid and 2% to 6.5% by mass of nitric acid.

8. The method for preparing an anode foil according to claim 1, characterized in that: The preparation method further comprises performing post-processing after the secondary hole expansion process; Preferably, the treatment liquid used in the post-treatment is an aqueous solution containing nitric acid; Preferably, the post-treatment temperature is 60°C to 90°C; Preferably, the post-treatment time is 1 min to 10 min; preferably 2 min to 5 min; Preferably, the mass percentage of nitric acid in the post-treatment solution is 2% to 11%.

9. An anode foil, characterized in that: The anode foil is prepared by the preparation method described in any one of claims 1 to 8.

10. An aluminum electrolytic capacitor, characterized in that: It comprises the anode foil according to claim 9 or the anode foil prepared by the preparation method according to any one of claims 1 to 8.